Association of single-nucleotide polymorphism of melanocortin-4 receptor (MC4R) with carcass traits in commercial rabbits under tropical conditions - Setiaji, A.; Kamila, F. T.; Mustofa, F.; Lestari, D. A.; Kamalludin, M. H.; Sutopo, S. (Veterinary World, 2025)
Background and Aim: Rabbits are increasingly valued in tropical livestock systems for their efficient feed conversion, high-quality meat, and adaptability to small-to-medium scale farming. Genetic selection using molecular markers, such as single-nucleotide polymorphisms (SNPs) in candidate genes, offers a powerful tool to enhance carcass yield and meat quality. The melanocortin-4 receptor (MC4R) gene, a regulator of energy balance and feed intake, has been associated with growth and carcass traits in various livestock but remains underexplored in tropical rabbit production systems. This study aimed to investigate the association between MC4R SNPs and economically important carcass traits in three commercial rabbit breeds, New Zealand White (NZW), Hyla, and Hycole, raised under tropical conditions in Indonesia. Materials and Methods: Thirty-five male rabbits (10 NZW, 11 Hyla, 14 Hycole; aged 3-4 months) were selected from 621 bucks. DNA was extracted from blood samples, and a 127-base pair MC4R fragment was amplified by polymerase chain reaction and sequenced for SNP detection. Carcass traits measured included hot carcass weight, cold carcass weight, reference weight, carcass percentage, meat-to-bone ratio, and five commercial cut points (CP1-CP5). Association analysis between MC4R genotypes (AA, AG, GG) and carcass traits was performed using a general linear model, considering breed and genotype × breed interactions. Results: An SNP at position 519 (G>A) produced three genotypes. GG-genotype rabbits exhibited the highest carcass percentage (57.0%) and superior CP2 weight (0.12 ± 0.03 kg) and percentage (10.67 ± 1.53%), with significant genotype effects (p < 0.05) for CP2 weight and CP1 percentage. Breed effects were significant for carcass percentage and CP1 percentage (p < 0.05), while genotype × breed interactions significantly influenced CP2 traits (p < 0.01). The G allele showed a positive association with forequarter meat yield, suggesting its utility in marker-assisted selection (MAS). Conclusions: MC4R polymorphism at position 519 is significantly associated with key carcass traits in commercial rabbits under tropical conditions. The GG genotype is linked to improved carcass yield, particularly in CP2 traits, although effects vary by breed. Incorporating this SNP into MAS programs can enhance meat production efficiency and carcass quality in tropical rabbit breeding.